1994
DOI: 10.1007/bf02412357
|View full text |Cite
|
Sign up to set email alerts
|

Extraosseous extension of Gaucher cell deposits mimicking malignancy

Abstract: Two cases are described in which patients with type I Gaucher disease developed extraosseous soft tissue masses consisting of Gaucher cell deposits. In one instance the mass destroyed the posterior cortex of the left distal femur and protruded into the soft tissues. In the second case the lesion involved the proximal tibia and gradually extended into the soft tissues. While the incidence of neoplastic disorder such as lymphoproliferative disease appears to be more common in Gaucher disease patients than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…A postulated mechanism for the cortical destruction necessary for extraosseous extension is the release of hydrolases and cytokines due to increased intramedullary pressure [3]. All four cases of extraosseous Gaucher disease found by Poll et al [3] as well as two cases reported by Hermann et al [5] and a case reported by Kaloterakis et al [8] described underlying marrow involvement and cortical disruption. To our knowledge, our patient is the only reported case of a subcutaneous Gaucher cell mass without extension from adjacent bone or lymph nodes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A postulated mechanism for the cortical destruction necessary for extraosseous extension is the release of hydrolases and cytokines due to increased intramedullary pressure [3]. All four cases of extraosseous Gaucher disease found by Poll et al [3] as well as two cases reported by Hermann et al [5] and a case reported by Kaloterakis et al [8] described underlying marrow involvement and cortical disruption. To our knowledge, our patient is the only reported case of a subcutaneous Gaucher cell mass without extension from adjacent bone or lymph nodes.…”
Section: Discussionmentioning
confidence: 94%
“…It is encountered amongst patients of Ashkenazi Jewish descent at a frequency ten times greater than that of the general population [5,6]. The disease is characterized by a deficiency of beta-glucocerebrosidase, which in turn leads to accumulation of glucocerebrosides (specifically glucosylceramide).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, hematoma/abcesses of the muscle (Jmoudiak et al 2003) or extraosseous manifestations (Poll et al 2000) which may mimic malignancy (Hermann et al 1994) are important differential diagnoses.…”
Section: Other Forms Of Bone Involvement In Gaucher Diseasementioning
confidence: 99%
“…MRI in Gaucher disease (Hermann et al 1986(Hermann et al , 1994 accurately depicts marrow and soft tissue damage secondary to infarction (Figure 15) and provides a crude estimate of the burden of Gaucher cells in the marrow. It should be used as a diagnostic adjunct in those patients with pinpointed skeletal involvement, e.g.…”
Section: Imaging Modalities For Skeletal Involvementmentioning
confidence: 99%